Revocation of personnel security clearances : analysis of departments of homeland security and defense - Black, Matthew C. (Defense, security and strategy series., 2015)
The Department of Homeland Security (DHS) and the Department of Defense (DOD) both have systems that track varying levels of detail related to revocations of employees' security clearances. DHS's and DOD's data systems could provide data on the number of and reasons for revocations, but they could not provide some data, such as the number of individuals who received a proposal to revoke their eligibility for access to classified information, which means that the total number of employees affected by the revocation process is unknown. Personnel security clearances allow people access to classif.